Effects of the community-based Wellspring Cancer Exercise Program on functional and psychosocial outcomes in cancer survivors - Santa Mina, D. (Curr Oncol, 2017)
PURPOSE: In this study, we examined the effects of a 30-week community-based exercise program on cancer-related fatigue, quality of life, and other health-related outcomes in a sample of adults with mixed cancer diagnoses. METHODS: This prospective cohort study looked at outcomes for participants involved in the Wellspring Cancer Exercise Program in southern Ontario. The program consisted of an initial phase of two supervised sessions weekly for 10 weeks and a transition phase of one supervised session weekly for the subsequent 20 weeks. Outcomes were measured at baseline and every 10 weeks throughout the intervention, as well as at 16 weeks after program completion. RESULTS: During a period of 13 months, 229 of the 355 cancer survivors who enrolled in the exercise program consented to participate in the study. Participants attended 71% of the supervised exercise sessions in the initial phase and 49% in the transition phase. From baseline to the end of the initial phase, significant improvements in cancer-related fatigue, 6-minute walk test, social well-being, systolic blood pressure, balance, and physical activity volume were observed. During the transition phase, health-related quality of life and emotional well-being improved significantly. CONCLUSIONS: The Wellspring Cancer Exercise Program is associated with clinically meaningful improvements in cancer-related fatigue and functional aerobic capacity. Several other aspects of well-being in cancer survivors also improved for participants in the program. Community-based cancer exercise programs such as the Wellspring Cancer Exercise Program can improve well-being for cancer survivors and can provide an effective option that enhances sustainability and accessibility to exercise services for this population.